Study on elastic properties of re-entrant regular tetrahedral cell of novel negative poisson ratio materials - LIU Yule; DENG Xianpu; QIE Yanhui; BAN Baowang (Jixie qiangdu)
In order to improve the mechanical properties of three-dimensional negative Poisson ratio materials, and expand the application of negative Poisson ratio materials. A new unit cell of negative Poisson ratio structural material was proposed by introducing internal concave angles into the edges of tetrahedral porous structures, and 7 kinds of orthogonal isotropic and orthogonal anisotropic enhancement designs were carried out on it. The influence of cell geometry parameters on the dimension one equivalent elastic modulus and Poisson ratio of new and enhanced cells was studied by using the homogenized finite element method and periodic boundary conditions， and the 3D printed resin sample was used for experimental verification. Compared with the existing negative Poisson ratio unit cells, the novel unit cell can save 50% of materials while maintaining the negative Poisson ratio characteristics. The three reinforcement schemes in x-direction, y-direction and xy-direction can significantly improve the bearing-load capacity while improving the negative Poisson ratio characteristics.